O conceito de região em três registros. Exemplificando com o Nordeste brasileiro - José William Vesentini (Confins)
This essay is a reflection on regionalization which makes use of Northeast Brazil as an example. It compares the regionalization in geography with periodization in history showing that, in both procedures, there are subjective and objective elements. It also contains a critical summary of three main conceptions concerning the Northeast region: one of them is traditional and focus on the landscape; the other one is modern and its concerns lay on the territorial division of labor; finally, the last one is postmodern and puts emphasis on the fact that this region has been an invention – produced by certain politicians, intellectuals and the media – since the 1920’s. At the end of this article there is a review showing the pros and cons of each of these regional conceptions.